2016
DOI: 10.1093/mnras/stw701
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear tides in a homogeneous rotating planet or star: global modes and elliptical instability

Abstract: We revisit the global modes and instabilities of homogeneous rotating ellipsoidal fluid masses, which are the simplest global models of rotationally and tidally deformed gaseous planets or stars. The tidal flow in a short-period planet may be unstable to the elliptical instability, a hydrodynamic instability that can drive tidal evolution. We perform a global (and local WKB) analysis to study this instability using the elegant formalism of Lebovitz & Lifschitz. We survey the parameter space of global instabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 55 publications
9
43
0
Order By: Relevance
“…This phenomenon has already been noticed in previous global analyses performed at lower degrees n 7 (e.g. Kerswell 1993b; , 2013Vantieghem et al 2015;Barker et al 2016). Indeed, more resonances are expected when n increases.…”
Section: Global Methods In Triaxial Ellipsoidssupporting
confidence: 79%
See 2 more Smart Citations
“…This phenomenon has already been noticed in previous global analyses performed at lower degrees n 7 (e.g. Kerswell 1993b; , 2013Vantieghem et al 2015;Barker et al 2016). Indeed, more resonances are expected when n increases.…”
Section: Global Methods In Triaxial Ellipsoidssupporting
confidence: 79%
“…The other monomials, denoted h i (r), contain z as factor. We index the set of these polynomials as (Lebovitz 1989;Barker et al 2016)…”
Section: Global Methods In Triaxial Ellipsoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tidal force field is represented in figure 2 and bears two important symmetries: it is invariant by rotation around the planet-moon axis (OX ) and by reflection relative to the (Y OZ) plane. The deformation induced by the tidal potential (1) can be analytically determined (see for instance discussions in Barker (2016) and Barker et al (2016)). At the lowest order, it can be shown that the planet adopts an ellipsoidal shape; the combination of both equatorial -or rotational-and tidal bulges forces the three axes of this ellipsoid to have different lengths.…”
Section: The Shape Of a Planet Undergoing Tidal Distortionmentioning
confidence: 99%
“…However, in some cases can tidal force frequencies intrude into the frequency range of the planet normal modes. For example, the tidal force on a rapid rotating planet can excite normal modes of the planet (Braviner and Ogilvie, 2014a, b;Barker et al, 2016). Interaction between Saturn ring and Saturn can excite acoustic free oscillation of Saturn (Marley, 1991;Marley and Porco, 1993;Marley, 2014).…”
Section: Introductionmentioning
confidence: 99%